PRE-SERVICE MATHEMATICS TEACHER’S ABILITY IN DESIGNING MATHEMATICAL TASK: AN ANALYSIS OF LESSON PLANS - Mahfudy, Sofyan; Mauliddin, Mauliddin (Universitas Bhinneka PGRI, 2024)
Mathematical tasks have an essential role in the mathematics learning process. Well-designed mathematical tasks will provide a learning opportunity for students to develop their mathematical ideas. The ability of pre-service mathematics teachers to design mathematical tasks during their academic studies significantly influences how they teach in actual learning. One of the ways to investigate pre-service mathematics teachers' ability to design tasks is by analyzing the tasks in the lesson plans they proposed. This study aims to scrutinize the level of cognitive demand for mathematics tasks designed by pre-service mathematics teachers in their lesson plans to get a thorough understanding of their ability to design tasks. This descriptive qualitative research analyzed mathematical tasks in 25 lesson plans proposed by pre-service mathematics teachers using the framework developed by Stein and Smith (1998). The results of this study show that most pre-service teachers designed tasks with a lower cognitive demand classification with types of memorization and procedures without connections. The mathematical tasks designed by pre-service mathematics teachers also have yet to lead to argumentation and the development of mathematical ideas through exploration or doing mathematics. Thus, based on the findings in this study, designing mathematics tasks with the potential to promote students' mathematical understanding remains a challenge for pre-service mathematics teachers. This article discusses and presents the implications of research results and recommendations for designing mathematical tasks.